Knowledge, Attitudes, and COVID-19 Prevention Practices of Healthcare Workers in Indonesia: A Mobile-based Cross-sectional Survey - Besral, Besral; Wiyanti, Zulvi; Nurizin, Dion Zein; Herdayati, Milla; Sutiawan, R; Rahmaniati, Martya; Yuniar, Popy (Kesmas, 2022)
Knowledge of disease can affect attitudes and prevention practices, and wrong attitudes and practices can directly increase the risk of disease infection. This study aimed to describe the knowledge, attitudes, and COVID-19 prevention practice of healthcare workers in Indonesia and factors associated with prevention practices. A mobile-based cross-sectional survey was conducted in August 2020 with 254 healthcare workers in Indonesia. The self-administered questionnaire consisted of four parts: 1) sociodemographic information, 2) knowledge of COVID-19, 3) attitudes and anxiety toward COVID-19, and 4) COVID-19 prevention practices. The results indicated that healthcare workers in Indonesia had excellent knowledge and positive attitudes about COVID-19, but their preventionpractices were lacking. The multiple logistic regression analysis results revealed that the factors associated with the COVID-19 prevention practices of healthcare workers in Indonesia were knowledge, attitudes, anxiety, domicile island, age, income, and education. Healthcare workers who had excellent knowledge, positive attitudes, and high anxiety exhibited better COVID-19 prevention practices than others. Healthcare workers in Sumatra Island, aged 41–50 years, and an undergraduate education showed better COVID-19 prevention practices than others.